OPTIMASI ASAM STEARAT DAN TEA PADA FORMULA SEDIAAN KRIM EKSTRAK KULIT PISANG KEPOK (Musa paradisiaca L.) - Saryanti, Dwi; Setiawan, Iwan; Safitri, Romadona Ayu (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2019)
Banana kepok peel has flavonoid compounds used as antioxidants. The aim of this research is to get optimum formula of cream by combination of stearic acid and trietanolamin on good physical propertie of cream. Cream was made with stearic acid 15% minimum concentration and maximum concentration 17%, triethanolamine with minimum concentration 2% and maximum concentration 4%. The optimization of the formula was using the simplex lattice design method with parameters are pH, viscosity, spreadability, adhesion and protection. The optimum cream formula on the combination of stearic acid 16.7 grams and triethanolamine 2.3 grams. Verification results of optimal formula cream for pH got 6.1, viscosity 237.47, adhesion 12.32, power spread 18.11, protection 14.98 which showed no significant difference in the test, and has good stability.